Utilization Digital Marketing In Increase Sales - Hasan, Liestiani (Doctoral Program of Social Science Pasundan University, 2025)
In the current digital era, the rapid development of technology has significantly transformed marketing strategies across industries. Digital marketing has emerged as one of the most effective methods to engage with consumers, build brand awareness, and ultimately drive sales growth. This study explores the utilization of digital marketing as a strategic tool to increase sales performance in competitive markets. By leveraging platforms such as social media, search engines, email marketing, and online advertising, businesses can reach targeted audiences with personalized messages, track consumer behavior, and optimize marketing efforts in real time. The research highlights several core components of digital marketing, including content marketing, SEO (Search Engine Optimization), SEM (Search Engine Marketing), influencer partnerships, and data-driven analytics. The integration of these tools enables companies to enhance customer engagement, increase conversion rates, and reduce customer acquisition costs. Furthermore, the flexibility and scalability of digital marketing campaigns allow for continuous improvement based on measurable outcomes. Case studies and empirical data presented in this paper demonstrate that companies which effectively implement digital marketing strategies often experience higher customer retention and significant sales growth compared to those relying solely on traditional marketing methods. The findings underline the critical role of digital marketing not only as a promotional tool but also as a strategic component of business development. This abstract concludes that the utilization of digital marketing is no longer optional but essential for companies aiming to remain competitive, customer-focused, and financially sustainable in the digital economy